Construction project organisation for 3D printing technology - Nikola Spicek; Mladen Radujkovic; Miroslaw J. Skibniewski (Građevinar)
The integration of three-dimensional (3D) printing technology into construction projects potentially yields many benefits, such as reduced site labour requirements, safer manoeuvring of project deadlines and budgets, and more effective waste management. However, the momentum of technology is not as expected owing to the lack of standardised processes and methodologies, and challenges imposed by the new technology. The organisational structure of such projects must be comprehensively studied. Studies on construction projects using the 3D printing technology are lacking. This study reviews the existing studies and three different case studies in Germany, United Kingdom, and United States of America to explore the primary differences between the roles, responsibilities, and interactions of key project participants within the organisational structure of construction projects using the 3D printing technology. The roles and responsibilities of clients/investors, project manager/construction managers, architects, structural engineers, quantity surveyor/project supervisor, and contractors/main contractors have been considered. Therefore, all features of the role of key participants and responsibilities to the new momentum created by this emerging technology must be aligned; otherwise, the combination of new technology and conventional organisation will reduce the value created by the new technology.